Beyond Light: Insights Into the Role of Constitutively Photomorphogenic1 in Plant Hormonal Signaling - Wang, Wenjing; Chen, Qingbin; Botella, José Ramón; Guo, Siyi (Frontiers in Plant Science, 2019)
Light is an important environmental factor with profound effects in plant growth and development. Constitutive photomorphogenic 1 (COP1) is a vital component of the light signaling pathway as a negative regulator of photomorphogenesis. Although the role of COP1 in light signaling has been firmly established for some time, recent studies have proven that COP1 is also a crucial part of multiple plant hormonal regulatory pathways. In this paper we review the available evidence involving COP1 in hormone signaling, its molecular mechanisms, and its contribution to the complicated regulatory network linking light and plant hormone signaling.